Identification of Key eRNAs for Spinal Cord Injury by Integrated Multinomial Bioinformatics Analysis - Huang, Runzhi; Wang, Siqiao; Zhu, Rui; Xian, Shuyuan; Huang, Zongqiang; Cheng, Liming; Zhang, Jie (Frontiers in Cell and Developmental Biology, 2021)
Background: Spinal cord injury (SCI) is a severe neurological deficit affecting both young and older people worldwide. Potential role of key eRNAs in SCI remains elusive, which is a prominent challenge in trauma repair process. This study aims to investigate the roles of key eRNAs, transcription factors, signaling pathways, and small-molecule inhibitors in SCI using multi-omics bioinformatics analysis. Methods: Microarry data of peripheral blood mononuclear cells (PBMC) samples from 27 healthy volunteers and 25 chronic phase SCI patients were retrieved from the Gene Expression Omnibus database. Differentially expressed transcription factors (DETFs), enhancer RNAs (DEeRNAs), and target genes (DETGs) were identified using the limma package. Fraction of immune cells was estimated using CIBERSORT algorithm. Gene Set Variation Analysis (GSVA) was applied to identify the downstream signaling pathways. The eRNA regulatory network was constructed based on the correlation results. Connectivity Map (CMap) database was used to find potential drugs for SCI patients. The cellular communication analysis was performed to explore the molecular regulation mechanism of SCI based on scRNA-seq data. Chromatin Immunoprecipitation Sequencing (ChIP-seq) and Assay for Transposase-Accessible Chromatin Using Sequencing (ATAC-seq) data were used to validate the key regulatory mechanisms. Single-cell RNA-seq dataset was used to validate the cell subtype localization of the key eRNAs. Results: In total, 21 DETFs, 24 DEeRNAs, and 829 DETGs were identified. A regulatory network of 13 DETFs, 6 DEeRNAs, 7 DETGs, 2 hallmark pathways, 2 immune cells, and 6 immune pathways was constructed. The link of SFPQ (TF) and VOPP1 (eRNA) (R = 0.990, p < 0.001, positive), VOPP1 (eRNA) and EGFR (target gene) (R = 0.974, p < 0.001, positive), VOPP1 and T helper (Th) cells (R = -0.987, p < 0.001, negative), and VOPP1 and hallmark coagulation (R = 0.937, p < 0.001, positive) was selected. Trichostatin A was considered as the best compound target to SCI-related eRNAs (Specificity = 0.471, p < 0.001). Conclusions: VOPP1, upregulated by SFPQ, strengthened the transient expression of EGFR. Th cells and coagulation were the potential downstream pathways of VOPP1. This regulatory network and potential inhibitors provide novel diagnostic biomarkers and therapeutic targets for SCI.